1977
DOI: 10.1901/jaba.1977.10-665
|View full text |Cite
|
Sign up to set email alerts
|

AN EXPERIMENTAL ANALYSIS OF ELECTRICITY CONSERVATION PROCEDURES1

Abstract: Daily electricity consumption of four families was recorded for 106 days. A reversal design, consisting of various experimental conditions interspersed between repeated baseline conditions, was used. During experimental conditions, daily prompts (written conservation slogans attached to front doors) and/or daily feedback (daily kilowatts consumed and daily cost information) were in effect. Maximum consumption occurred during the initial baseline; minimum consumption occurred during different experimental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Several studies have demonstrated that regular feedback on energy use can reduce consumption (Becker, 1978;Hayes & Cone, 1977;Kohlenberg, Phillips, & Proctor, 1976;Palmer, Lloyd, & Lloyd, 1978;Seligman & Darley, 1977;Winett, Kaiser, & Haberkorn, 1977;Winett, Neale, & Grier, 1979). Monetary rebates based on decreases in energy consumption have also been shown to be effective means of reducing residential energy use (Winett, Kagel, Battalio, & Winkler, 1978;Winett & Nietzel, 1975 There is a category of residential units in which there is someone with a strong interest in getting residents to conserve energy.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that regular feedback on energy use can reduce consumption (Becker, 1978;Hayes & Cone, 1977;Kohlenberg, Phillips, & Proctor, 1976;Palmer, Lloyd, & Lloyd, 1978;Seligman & Darley, 1977;Winett, Kaiser, & Haberkorn, 1977;Winett, Neale, & Grier, 1979). Monetary rebates based on decreases in energy consumption have also been shown to be effective means of reducing residential energy use (Winett, Kagel, Battalio, & Winkler, 1978;Winett & Nietzel, 1975 There is a category of residential units in which there is someone with a strong interest in getting residents to conserve energy.…”
mentioning
confidence: 99%
“…A preliminary effort was made by Palmer, Lloyd, and Lloyd (1977). They tested the effects of daily feedback expressed in either monetary of kWh form.…”
mentioning
confidence: 99%
“…Effects have been obtained with feedback given continuously (Kohlenberg, Phillips, & Proctor, 1976); daily (e.g., Hayes & Cone, 1977;Palmer et al, 1977); four times each week (Seligman & Darley, 1977) and, in the case of fuel oil, as infrequently as only once in several months (Seaver & Patterson, 1976 Fitch, 1977) or (b) give feedback monthly. Hayes (1977) and Winett, Neale, and Grier (1979) have generated preliminary data supportive of the first alternative; the present study is designed to investigate the second.…”
mentioning
confidence: 99%
“…For example Palmer, Lloyd and Lloyd (1977) used behavioral intervention techniques such as various forms of prompting and feedback to achieve a mean reduction in daily electricity use of 35% on a sample of four families, also illustrating some reversal of intervention effects during periods when interventions were removed. Becker (1978) used feedback interventions to achieve reductions of 5-15% in energy use.…”
Section: The Contribution Of Behavior Analysis To Ecopsychologymentioning
confidence: 99%
“…However, in the Becker study, as in that by Palmer et al (1977), feedback was provided by researchers attaching notices to participants' front doors on a daily basis, making it time and resource intensive to administer on a large scale. Hayes and Cone (1981) illustrated the effectiveness of more economical forms of feedback using monthly letters to participants, comparing the previous month's use to the same month during a preceding baseline period.…”
Section: The Contribution Of Behavior Analysis To Ecopsychologymentioning
confidence: 99%